PENGARUH LATIHAN SQUAT JUMP DAN BOX JUMP TERHADAP KETERAMPILAN LONG PASS PADA PERMAINAN SEPAK BOLA - Wawan Kurniawan; Andika Triansyah; Mimi Haetami (Universitas Tanjungpura, 2019)
AbstractThe problem in this study was whether there is an influence of differences in squat jump and box jump exercises on long pass skills in soccer games. This study aimed to determine the effect of different squat jump and box jump exercises on long pass skills in soccer games.The method in this study used the experimental method with the form of one group pretest posstest design. The population in this study was extracurricular students of SMP N 6 Kab. Ketapang. The number of samples in this study were 40 participants. The instrument used is the remote kick test column. Data analysis using t test analysis (influence test).Based on the calculation of the data obtained passing soccer skills with the results of t test (influence test), T count equal to 10,408 and T table equal to 2,052 can be hypotheses t count> t table (6,676> 1,997). That is, there was the effect of the squat jump exercise with an increase in percentage of 16%, there is the effect of box jump training on long pass skills of 6%, meaning that squat jump training is better used in increasing long pass kick skills. Keywords: Box Jump, Long Pass, Squat Jump